Tinjauan Strategi Promosi pada Karya Mebel Tasikmalaya - Ujang Irman; Annisa Desty Puspatriani; Wirasujatma, Muis (EKOBIMA, 2024)
Currently, many promotions are carried out using digital media which are easier to use and save costs. This promotion can be said to be more effective when compared to promotions such as personal selling, direct selling and distributing brochures in general. This promotional technique is called digital marketing.This research aims to determine the promotional strategy carried out by Karya Mebel Tasikmalaya in direct promotion. This research is qualitative research with data collection carried out using literature study methods and interviews with the owners of the Karya Mebel Tasikmalaya company.Based on the research results, it can be concluded that the promotional strategy carried out by Karya Mebel Tasikmalaya has been implemented well, because it is in accordance with the promotional mix.